"Fracturoscopy" is Superior to Fluoroscopy in the Articular Reconstruction of Complex Tibial Plateau Fractures—An Arthroscopy Assisted Fracture Reduction Technique. Issue 8 (August 2016) - Krause, Matthias; Preiss, Achim; Meenen, Norbert M.; Madert, Jürgen; Frosch, Karl-Heinz
Abstract : Objective: To analyze the anatomic accuracy of fracture reduction controlled by fluoroscopy as compared with arthroscopically assisted reduction ("fracturoscopy") in patients with complex tibial plateau fractures (AO/OTA 41-C). Quality of fracturoscopy-guided reduction was checked with postoperative computed tomography. Design: Prospective observational study. Setting: Urban level 1 trauma center. Patients: Seventeen consecutive patients, with a complex, bicondylar tibial plateau fracture. Intervention: The intraoperative, open insertion of an arthroscope (2.4-mm or 2.8-mm optics), to visualize the articular surface and fracture reduction. Main Outcome Measurements: Ability to detect residual fracture depression or gap after previous open reduction under fluoroscopic guidance. Results: An open fracture reduction with fluoroscopic guidance was performed in all cases. In 7 cases, open reduction and fluoroscopy resulted in satisfactory fracture reduction (fluoroscopy group). In 10 of 17 cases, subsequent "fracturoscopy" showed persistent fracture depression (≥2 mm, fracturoscopy group) with the need for intraoperative correction. Patients in the fracturoscopy group demonstrated significantly greater preoperative fragment depression (12.55 ± 6.56 mm) and a larger preoperative fracture gap (7.83 ± 5.49 mm) compared with patients with a satisfactory reduction under fluoroscopy (depression 4.97 ± 4.02 mm, P = 0.016; gap 2.47 ± 1.07 mm, P = 0.023). Fluoroscopy was not successful in achieving satisfactory reduction in cases in which the postero-latero-central region was affected ( P = 0.004, χ 2 test). Postoperative computed tomography demonstrated satisfactory articular reconstruction in all cases. Conclusions: Intraoperative fracturoscopy permitted a significantly improved visualization of fracture fragment displacement, specifically in the postero-latero-central region of the tibial plateau, as compared with fluoroscopy. Fracturoscopy is recommended for fractures involving the postero-latero-central region of the tibial plateau. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.